An integral interpolation chain fraction of the Thiele type - Makarov, V. L.; Demkiv, I. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
An integral interpolation chain fraction of the Thiele type has been constructed. This fraction is a natural generalization of the classical Thiele contiunued fraction.